2018
DOI: 10.1177/0269215518775156
|View full text |Cite
|
Sign up to set email alerts
|

Hand-Use-at-Home Questionnaire: validity and reliability in children with neonatal brachial plexus palsy or unilateral cerebral palsy

Abstract: Objective:To investigate construct validity and test–retest reliability of the parent-rated Hand-Use-at-Home questionnaire (HUH) in children with neonatal brachial plexus palsy or unilateral cerebral palsy.Design and subjects:For this cross-sectional study, children with neonatal brachial plexus palsy or unilateral cerebral palsy, aged 3–10 years, were eligible.Main measures:The HUH, Pediatric Outcome Data Collection Instrument Upper Extremity Scale (neonatal brachial plexus palsy only), and Children’s Hand-Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“… Reliability Inadequate + Hypotheses testing for construct validity: convergent validity Adequate ? HUH Van der Holst et al [ 44 ] Reliability Doubtful + Measurement error Doubtful ? Hypotheses testing for construct validity: convergent validity Very good 5 + Hypotheses testing for construct validity: discriminative validity Very good Geerdink et al [ 35 ] PROM development Doubtful Structural validity Adequate ?…”
Section: Resultsmentioning
confidence: 99%
“… Reliability Inadequate + Hypotheses testing for construct validity: convergent validity Adequate ? HUH Van der Holst et al [ 44 ] Reliability Doubtful + Measurement error Doubtful ? Hypotheses testing for construct validity: convergent validity Very good 5 + Hypotheses testing for construct validity: discriminative validity Very good Geerdink et al [ 35 ] PROM development Doubtful Structural validity Adequate ?…”
Section: Resultsmentioning
confidence: 99%
“…Another limitation of our study is that we did not systematically document whether the use of the hand was reduced, but rather documented it anecdotally when parents reported it during visits to our clinic. Future studies should include patient-reported outcome measures; for example, the Hand-Use-at-Home questionnaire to document the frequency of hand employment ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…For individual children, the minimal detectable change of the HUH is 1.66 logits. 15 For none of the children was an effect of this magnitude found (Table 2).…”
Section: Hand-use-at-home Questionnaire (Huh)mentioning
confidence: 95%
“…Test-retest reliability and construct validity of this Dutch questionnaire in children with CP are very good and good, respectively. 14,15 Lifestyle Assessment Questionnaire for CP (LAQ-CP): The child's participation was assessed through the LAQ-CP, a parent-reported questionnaire. The LAQ-CP consists of 46 items and examines the impact of the disabilities on six dimensions.…”
Section: Parent-rated Outcomes At Child Level Canadian Occupational Performance Measure (Copm)mentioning
confidence: 99%